THE PERSPECTIVE OF JAPAN HOME COUNTRY COMPANY TO THE PERFORMANCE EVALUATION OF SUBSIDIARIES COMPANY IN INDONESIA - Sherly Octaviani (Universitas muhammadiyah malang, 2014)
The purpose of this study is to determine the financial performance of subsidiaries of Japanese multinationals operating in Indonesia from the perspective of the Japanese parent company and to find out which one of the company’s financial performance had morehealthy during the year 2010 until 2012. The analytical tool used in this study to translate is to use the current rate method, and the analytical tools used to measure the financial performance of subsidiaries of multinational Japanese was by using financial ratio analysis, and to reject the measure using the method of time series and cross section.The result show that there was conducted on the financial report of a subsidiaries of the Japanese multinational operating in Indonesia by limiting the study period from 2010 until 2012. Based on the financial results of the Japanese multinational subsidiaries operating in Indonesia, which had been translated and analyzed it could be seen that the financial performed of multinational subsidiaries of the sub sectors of ceramic, glass and porcelain which operates in Indonesia in 2010 until 2012 indicate unhealthy conditions. Keywords: Multinational corporation, translation of the financial statements, current rate method, exchange rate, ratio of financial.